2008
DOI: 10.1038/bmt.2008.382
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab purging and maintenance combined with auto-SCT: long-term molecular remissions and prolonged hypogammaglobulinemia in relapsed follicular lymphoma

Abstract: We enrolled 23 patients with relapsed follicular lymphoma (FL) in a prospective single-arm study of auto-SCT combined with in vivo rituximab graft purging and post transplant rituximab maintenance. Minimal residual disease was monitored with quantitative PCR testing. With a median follow-up of 74.2 months, neither median overall survival (OS) nor PFS has been reached. Here, 5-year OS and 5-year PFS are 78% (95% confidence interval (CI) 61-95%) and 59% (95% CI 38-80%), respectively. Time to progression (TTP) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 58 publications
1
38
0
1
Order By: Relevance
“…The safety findings in the present study did not differ from those previously reported (12), confirming the safety of rituximab in maintenance therapy. Treatment was delayed in only two patients due to rituximab toxicity.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The safety findings in the present study did not differ from those previously reported (12), confirming the safety of rituximab in maintenance therapy. Treatment was delayed in only two patients due to rituximab toxicity.…”
Section: Discussionsupporting
confidence: 70%
“…The use of rituximab for the in vivo purging of hematopoetic stem cell products has yielded encouraging results in disease eradication (up to 79% of MRD rendered undetectable after in vivo purging with rituximab), resulting in five-year OS and PFS of up to 78% (16)(17)(18)(19)). An ongoing prospective study in patients with relapsed follicular lymphoma showed that the use of rituximab for in vivo graft purging and maintenance therapy following auto-STC resulted in undetectable MRD in a high proportion of patients (12). In this study, MRD was present in 56.5% of the patients (13/23) prior to treatment, but became undetectable in 77% of the patients after auto-SCT and in another two patients after subsequent rituximab maintenance therapy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Both groups of patients tend to develop low IgM, but not IgG and IgA. In contrast, some patients with refractory follicular lymphoma treated with rituximab and HSCT developed persistently low IgA and IgG with recovery of IgM levels 34, 37. Underlying disease can therefore influence the development of isotype‐specific hypogammaglobulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three patients with relapsed FL were enrolled in this prospective single-arm study. 39 Five-year OS and 5-year PFS are 78% (95% confidence interval [CI] 61% to 95%) and 59% (95% CI 38% to 80%), respectively. Time to progression with the rituximab-containing regimen was significantly improved compared with each patient's previous treatment (P  0.001).…”
Section: Dovepressmentioning
confidence: 99%